Synergetic protective effect of berberine and ginsenoside Rb1 against tumor necrosis factor alpha−induced inflammation in adipocytes. Issue 2 (20th December 2021) - Cai, Zhixing; Chen, Yue
ABSTRACT: Obesity significantly impacts living a normal life by increasing morbidity. Additionally, obesity has been shown to be closely associated with severe inflammation in adipocytes. It is widely reported that berberine (BBR) has an anti-inflammatory effect and can reduce glucose and lipid accumulation, whereas ginsenoside Rb1 (Rb1) has been shown to have a significant inhibitory effect on insulin resistance and lipid peroxidation. In this study, we aimed to explore the synergetic effect of BBR and Rb1 on tumor necrosis factor alpha (TNF-α)-treated adipocytes and the mechanisms underlying it. We found that TNF-α reduced cell viability, facilitated the production of inflammatory factors, induced adipogenesis, activated the nuclear factor kappa B (NF-κB) pathway, and increased the expression of peroxisome proliferator-activated receptor gamma, CCAAT enhancer-binding protein alpha, and sterol regulatory element-binding protein-1 c in adipocytes. However, these effects were significantly alleviated by BBR or Rb1. Additionally, a synergetic effect was observed when BBR and Rb1 were used in combination. The effects of BBR in combination with Rb1 on cell proliferation, inflammation, adipogenesis, and the NF-κB pathway in TNF-α-treated adipocytes were significantly abolished by receptor activator of nuclear factor kappa-Β ligand, which is an activator of the NF-κB pathway. Collectively, the results revealed that BBR and Rb1 have a synergetic protective effect against TNF-α-induced inflammation in adipocytes. The mechanism underlying this synergetic effect was found to be inhibition of the NF-κB signaling pathway.